BEYOND THE FEED: THE POWER OF POLITICAL INFLUENCERS IN FRAMING ELECTION NARRATIVES - Prasetya Yoga Santoso (Journal of Scientech Research and Development, 2023)
The development of digital communication technology has shifted the electoral campaign landscape from physical spaces to cyberspace through the involvement of digital influencers. This study aims to analyze the strategies used by influencers to construct political narratives on social media and their implications for shaping public opinion ahead of the General Election. Using a qualitative approach with a descriptive analytical design, this research focuses on the textual analysis of digital documents through non-participant observation (netnography) of content posts, captions, and comment threads on social media platforms, without the use of field interviews or respondent sampling. The results show that political influencers effectively act as new opinion leaders, packaging rigid public policy issues into popular content (infotainment) through three main pillars: humanistic personification of candidates, policy simplification, and counter-narrative advocacy. Analysis of digital comment threads reveals that the cyberspace beneath influencer posts functions as an arena for opinion consolidation, rich in emotional engagement, despite being vulnerable to distortion due to echo chamber effects and platform algorithm bias. These findings conclude that the involvement of political influencers has confirmed a radical shift in digital agenda-setting theory and the two-stage communication flow, where they are no longer merely campaign support instruments but rather determining pillars in directing support for modern digital democracy.